Egg-inspired engineering in the design of thin-walled shelled vessels: a theoretical approach for shell strength - Narushin, Valeriy G.; Romanov, Michael N.; Griffin, Darren K. (Frontiers in Bioengineering and Biotechnology, 2022)
A novel subdiscipline of bionics is emerging in the form of ‘egg-inspired engineering’ through the use of egg-shaped ovoids as thin-walled tanks and building structures. Hügelschäffer’s and Narushin’s models of egg geometry are highly applicable within this proposed subdiscipline. Here we conducted a comparative analysis between the two models with respect to some of the most important egg parameters. These included contents volume, shell volume, and the location of the neutral axis along the shell thickness. As a first step, theoretical studies using the Narushin’s model were carried out due to the lack (or limited amount) of data on the geometric relationships of parameters and available calculation formulae. Considering experimental data accumulated in the engineering and construction industries, we postulate a hypothesis that there is a correlation between location of the neutral axis and the strength of the walls in the egg-shaped structure. We suggest that the use of Narushin’s model is preferable to Hügelschäffer’s model for designing thin-walled shelled vessels and egg-shaped building structures. This is due to its relative simplicity (because of the requirement for only two initial parameters in the basic equation), optimal geometry in terms of material costs per unit of internal capacity, and effective prerequisites for shell strength characteristics.